EGCG identified as an autophagy inducer for rosacea therapy - Zhou, Lei; Zhong, Yun; Wang, Yaling; Deng, Zhili; Huang, Yingxue; Wang, Qian; Xie, Hongfu; Zhang, Yiya; Li, Ji (Frontiers in Pharmacology, 2023)
Background Rosacea is a common facial skin inflammatory disease featured with hyperactivation of mTORC1 signaling in the epidermis. Due to the unclear pathogenesis, the effective treatment options for rosacea remain limited. Methods WGCNA analyzed the relationship between epidermis autophagy and mTOR pathways in rosacea, and further demonstrated through immunofluorescence and qPCR analysis. A potential therapeutic agent for rosacea was predicted based on the key genes of WGCNA module. The in vivo and in vitro experiment was conducted to verify its therapeutic role. Drug-target prediction (TargetNet, Swiss, and Tcmsp) and molecular docking offered potential pharmacological targets. Results WGCNA analysis identified that epidermis autophagy was related to the activation of mTOR pathways in rosacea. Next, autophagy was downregulated in the epidermis of rosacea, which was regulated by mTOR. In addition, the vivo experiment demonstrated that autophagy induction could be an effective treatment strategy for rosacea. Subsequently, based on the key genes of WGCNA module, EGCG (epigallocatechin-3-gallate) was predicted as a potential therapeutic agent for rosacea. Furthermore, the therapeutic role of EGCG on rosacea was confirmed in vivo and vitro. Finally, drug-target prediction and molecular docking revealed that AKT1/MAPK1/MMP9 could be the pharmacological targets of EGCG in rosacea. Conclusions Collectively, our findings revealed the vital role of autophagy in rosacea and identified that EGCG, as a therapeutic agent for rosacea, attenuated rosacea-like inflammation via inducing autophagy in keratinocytes.